Chlorothalonil Exposure and Risk of Cancer : A Systematic Review and Meta-analysis Protocol - Soleimani, Yaser; Shahsavari, Mohammad Javad; Sadeghi, Hamid; Aryanejad, Ali; Qashami, Zeinab; Khazali, Alireza; Daraei, Mahdi; Noori, Narges; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Environment and Cancer, 2024)
Background: Chlorothalonil, a fungicide widely used in agriculture, has come under scrutiny due to concerns about its potential link to human cancer. Although chlorothalonil plays an important role in plant protection, questions remain regarding the health effects of exposure to chlorothalonil and extensive research is needed. This review and meta-analysis aimed to synthesize the existing evidence on the association between chlorothalonil exposure and cancer risk and to resolve the controversy in existing knowledge. Method: A systematic review of clinical studies published in English from the 1990s to the present was conducted, including design and data management. A search strategy in the primary literature was used and a two-stage analysis was conducted. A sampling design was used to extract data and a design tool was used to assess the quality of included studies. Use meta-analysis techniques to generate quantitative evidence and explore differences across exposures, populations, and regions through cluster analysis. Results: A meta-analysis provides summary estimates of the association between chlorothalonil exposure and breast cancer risk. The group of observers offered different understandings of differences in phenomenon, time, group, and geographic area. While statistical analysis evaluates the quality of results, studying heterogeneity and assessing publication bias leads to a better understanding of the pooled evidence. Conclusion: This systematic review and meta-analysis provides insight into the health effects of chlorothalonil exposure. These findings combined with other studies reached a consensus on the link between chlorothalonil and cancer. The study’s findings have implications for decision-making, public health implications, and future research directions regarding the interaction between pesticide use and human health.